1999
DOI: 10.3109/10428199909093723
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Typical and Atypical Chronic Lymphocytic Leukaemia

Abstract: Subdivision of CLL into typical and atypical subtypes, as proposed by the FAB group in 1989, is not yet widely accepted and its clinical significance is still debated. In recent years, however, a strong correlation was found between atypical morphology trisomy 12 and an aberrant immunophenotype. In the first part of this review we discuss current concepts and generally accepted data on morphology, immunophenotype, genetic abnormalities, clinical features and prognostic factors in CLL. Subsequently, based on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 66 publications
3
41
0
3
Order By: Relevance
“…In comparison with typical CLL, atypical CLL frequently expresses an aberrant immunophenotype and chromosomal abnormalities, especially trisomy 12, are more frequent in atypical CLL. 13 Moreover, atypical CLL is clinically more aggressive. The Matutes's CLL score allows …”
Section: Discussionmentioning
confidence: 99%
“…In comparison with typical CLL, atypical CLL frequently expresses an aberrant immunophenotype and chromosomal abnormalities, especially trisomy 12, are more frequent in atypical CLL. 13 Moreover, atypical CLL is clinically more aggressive. The Matutes's CLL score allows …”
Section: Discussionmentioning
confidence: 99%
“…3, 4, 5, and 7). 22 On immunophenotyping, all cases had a Matutes/Moreau score between 4/5 and 5/5, 23 indicative for CLL. Surface immunoglobulin staining for light chains showed a kappa positivity in three and a lambda positivity in four cases.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Criel et al [13,14] showed that certain patients even without an increased prolymphocyte population might have an accelerated poor clinical outcome. The immunophenotypic picture of the pathologic population with lymphocytes containing compact nucleoli in our group of patients, even though they looked like prolymphocytes, was characteristic for B-CLL but neither for prolymphocytic leukemia (PLL) nor transformation to this type of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical morphology usually is associated with poor clinical outcome of the disease [13,14,15,16]. In addition, the investigation of nucleolus, the very active and variable nuclear compartment, and its morphologic and functional changes assumed its usefulness in predicting the early disease progression probability [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation